Effects of Lactic Acid Bacteria on Fermentation and Nutritional Value of BRS Capiaçu Elephant Grass Silage at Two Regrowth Ages - Daiana Lopes Lelis; Mirton José Frota Morenz; Domingos Sávio Campos Paciullo; João Paulo Santos Roseira; Carlos Augusto de Miranda Gomide; Odilon Gomes Pereira; Jackson Silva e Oliveira; Fernando Cesar Ferraz Lopes; Vanessa Paula da Silva; Tâmara Chagas da Silveira; Fernanda Helena Martins Chizzotti (Animals)
The objective of this study was to evaluate the effects of lactic acid bacteria inoculation on the fermentation profile and nutritional value of BRS Capiaçu elephant grass silages harvested at two regrowth ages. The treatments were arranged in a 5 × 2 factorial scheme, with five inoculants (I) and two regrowth ages (A, 90 and 105 days), in a completely randomized design, with three replicates. There were I × A interactions (p < 0.05) on pH, acetic acid, and water-soluble carbohydrates. The silage treated with Kera-Sil showed a lower pH compared with the control silage. The highest ammonia nitrogen content was recorded in the silage treated with Yakult®. There were I × A interactions (p < 0.05) on the dry matter (DM) content, neutral detergent fiber (NDF), and in vitro digestibility of DM (IVDMD) and NDF (IVNDFD). Silages treated with Kera-Sil and Silo-Max at 90 days of regrowth showed a higher DM and higher IVDMD (p < 0.05). A higher NDF content and lower IVDMD and IVNDFD were recorded in silages produced with grass harvested at 105 days of regrowth (p < 0.05). The use of commercial microbial inoculants improved the fermentative and nutritional parameters of the silages.